Juridical Analysis of Tender Contract Law Enforcement According To Law Number 5 of 1999 Concerning Prohibition of Monopolistic Practices and Unfair Business Competition - Ariman, Renaldi; Arrisman, Arrisman; Gultom, Elisatris (Journal of Law, Politic and Humanities, 2025)
This paper analyzes several instances of bid rigging based on two KPPU case decisions: No. 04/KPPU-L/2020 involving procurement collusion in hospital projects in Langsa, Aceh, and No. 14/KPPU-L/2019 related to irregularities in the procurement of drinking water systems at Bandar Lampung. The research employs a normative legal methodology with a prescriptive and practical orientation. It adopts legal and case-based approaches. Legal materials referenced include primary, secondary, and tertiary sources, collected through a literature-based method. The study concludes that the decision in Case No. 04/KPPU-L/2020 adheres to the provisions of Article No. 22 of Law No. 5 of 1999 and KPPU Regulation No. 2 of 2010, which serves as the guideline for implementing said article. Meanwhile, in Case No. 14/KPPU-L/2019, the existence of post-tender cooperation between the government and private parties, which ignored previously agreed tender terms, constitutes a violation of Article 79 of Government Regulation No. 54 of 2010 concerning the evaluation of bids in public procurement.